2003
DOI: 10.1136/bjsm.37.5.464
|View full text |Cite
|
Sign up to set email alerts
|

Joint Conference of BASEM and BASES

Abstract: There is little information that the orthopaedic surgeon can provide for patients concerned about the effect of a total hip arthroplasty (THA) operation on their ability to continue playing golf and at what level they can hope to play.We present the results of a study into the effect of THA for osteoarthritis on the golfing habits and performance of 750 patients. We sent 750 patients a questionnaire, which enquired about their participation in golf before and after the operation. We received 698 replies, 66 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Despite the fact that treatment with Citrus bergamia extract in patients with dyslipidemia did not reduce BMI or BW after 12 weeks (Babish et al, 2016;Cai et al, 2017), its combination with Eurycoma longifolia has been suggested to improve BMI in obese patients. The bioactive fraction of peptides isolated from an aqueous extract of Eurycoma longifolia root (Sambandan, Rha, Aminudim, & J-M., 2006) has been reported to improve body composition, increase fat-free mass, reduce body fat, and increase muscle strength, and size compared to the placebo group in patients associated with intense strength training program (Hamzah, 2003). However, in the present trial, CitruSlim did not improve lean body mass, body fat percentage, and fat-free mass as measured by DXA during 112 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that treatment with Citrus bergamia extract in patients with dyslipidemia did not reduce BMI or BW after 12 weeks (Babish et al, 2016;Cai et al, 2017), its combination with Eurycoma longifolia has been suggested to improve BMI in obese patients. The bioactive fraction of peptides isolated from an aqueous extract of Eurycoma longifolia root (Sambandan, Rha, Aminudim, & J-M., 2006) has been reported to improve body composition, increase fat-free mass, reduce body fat, and increase muscle strength, and size compared to the placebo group in patients associated with intense strength training program (Hamzah, 2003). However, in the present trial, CitruSlim did not improve lean body mass, body fat percentage, and fat-free mass as measured by DXA during 112 days of treatment.…”
Section: Discussionmentioning
confidence: 99%